COMPARATIVE ANALYSIS OF PERCEPTIONS TOWARDS IT SECURITY IN ONLINE BANKING; STUDENTS OF MONTENEGRO VS. ALBANIAN STUDENTS - Makarevic, Nedim (European Scientific Journal, ESJ, 2015)
The purpose of this paper was to analyze and compare perceptions of Albanian students vs. students of Montenegro who are using online banking, to provide insight into similarities and differences of their view points and to create important set of information for all subjects active in banking industry. Survey based on six variables and specific questions assigned to each one of those variables was completed at high response rates, 207 respondents from Albania & 202 from Montenegro. Results were presented using descriptive statistics. Limitations of this research are relatively small sample and generic approach to problem. Suggestions for future researches would be based on going more deeply into the issue and analyzing larger samples. According to results, Albanian students were slightly more concerned and careful when dealing with online transactions compared to students of Montenegro who are more relaxed and perceive banks as reliable in assuring security of handling money and personal information online. Since there is gap in literature when it comes to research dealing with IT-security of online banking in both countries, this article is not only unique, but it may be stimuli for new research with different approaches in the future.